A influência dos hábitos de sucção não nutritiva, do padrão respiratório e do tamanho da adenóide no desenvolvimento das más oclusões na dentição decídua: estudo tipo caso-controle em pré-escolares de Juiz de ForaMG - Elton Geraldo de Oliveira Gois (2005)
The occlusal relation in primary dentition has been considered an important factor in recent researches, for its key role as a guide to the permanent dentition development. In that context, identify previous alterations in the normality pattern, together with the possible etiologic factors; have been carried out in a large amount of cases. For that matter, the aim of this study was to associate finger and pacifier sucking habits, breathing pattern, adenoids size and malocclusion in primary dentition, in children living in Juiz de Fora - MG, through a case-control study. Participated in the research 300 preschool children, with ages ranging from 3 to 6 years-old, randomly selected from state and private schools, matching according to age, sex and economical class. The data collection was reached through a questionnaire applied to the parents/responsible and by the childs clinical evaluation followed by an adenoid radiograph of the selected preschool children. All the instruments were previously tested in a study-pilot. The data were processed in the program Epi-Info 2000 and Statistical Package for Social Science 8.0 and applied chi-square and odds ratio tests and conditional multiple logistic regression analysis. The results pointed to the following independent risk factors for the malocclusion occurrence in preschool children: pacifier sucking period ending between 2 and 3 years of age (OR=4,5 [1,8-11,2] CI 95%), between 3 and 4 years of age (OR=26,6 [8,7-81,4] CI 95%), for more than 4 years of age (OR=35,5 [9,4-134,5] CI 95%) and mouth breathing pattern, clinically diagnosed (OR=9,3 [4,7-18,7] CI 95%). The hypertrophied adenoids and the digital sucking alone were not directly related to the studied malocclusion (p>0,05). In that way, it can be concluded that the malocclusion in the primary dentition was directly related to the pacifier sucking period for more than 2 years of age and to the mouth breathing pattern in preschool children, with ages ranging from 3 to 6 years-old in the city of Juiz de Fora.